Pengaruh Promosi dan Fasilitas terhadap Kepuasan Pengunjung pada Monaco Park Kabupaten Deli Serdang - Sasnita Simbolon; Riandani Rezki Prana; Husni Mubarak (Journal of Management and Economics Research, 2022)
The purpose of this Research was to know how much influence promotions and facilities on satisfaction of visitor at Monaco park in Kabupaten Deli Serdang. The research sample were 90 people whose research was conducted from May to June 2019, Sampling used accidental sampling (sample accidental meet), which was the sample by taking samples to anyone who was in a place or chance to meet as a sample that was deemed suitable as a data source. Data analysis used multiple linear regression, hypothesis testing used test coefficient of determination (R2), simultaneous test (F test), partial test (t test), while processing data used SPSS 16. The results showed that promotion and facilities were able to explain their existence to the variable visitor satisfaction, besides that, simultaneously the promotion variables and facilities have a positive and significant effect on visitor satisfaction. While partially promotion variable has not affect visitor satisfaction, while partially facility variables have a positive and significant effect on visitor satisfaction at Monaco park in Kabupaten Deli Serdang